2016
DOI: 10.1002/2016sw001471
|View full text |Cite
|
Sign up to set email alerts
|

What if we had a magnetograph at Lagrangian L5?

Abstract: Synoptic Carrington charts of magnetic field are routinely used as an input for modelings of solar wind and other aspects of space weather forecast. However, these maps are constructed using only the observations from the solar hemisphere facing Earth. The evolution of magnetic flux on the “farside” of the Sun, which may affect the topology of coronal field in the “nearside,” is largely ignored. It is commonly accepted that placing a magnetograph in Lagrangian L5 point would improve the space weather forecast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In the recent paper by Mackay et al (2016) it has been shown that such L5 observations could increase the accuracy of global quantities relevant to eruptions on the Sun by anywhere from 26-40%. Pevtsov et al (2016) reports similar improvements for the estimations of solar wind and plasma outflows as well. -Identification of erupting flux ropes.…”
Section: Producing An Operational Modelsupporting
confidence: 60%
“…In the recent paper by Mackay et al (2016) it has been shown that such L5 observations could increase the accuracy of global quantities relevant to eruptions on the Sun by anywhere from 26-40%. Pevtsov et al (2016) reports similar improvements for the estimations of solar wind and plasma outflows as well. -Identification of erupting flux ropes.…”
Section: Producing An Operational Modelsupporting
confidence: 60%
“…A continuous view of the solar poles is particularly compelling, both for space-weather monitoring and for establishing the nature of the solar dynamo. There are also mission concepts that would provide new insights while stopping short of full 4π coverage, such as an early-warning system at the Earth-Sun L5 point (e.g., Pevtsov et al 2016), or a two-spacecraft system that would improve upon STEREO's initial exploration of stereoscopic imaging (Strugarek et al 2015). Sustained multi-vantage observations of the photospheric magnetic field, the inner boundary of the heliosphere, has transformative potential.…”
Section: Observational Improvementsmentioning
confidence: 99%
“…Such comparisons are imperfect, and a one-to-one correspondence between EUV-dark regions in the images and open-flux domains from the model is not expected (see Lowder et al 2014Lowder et al , 2017. Several reasons probably account for these discrepancies: (1) Pevtsov et al 2016). Structures in the eastern hemisphere may be ad-versely affected when there is a significant amount of flux at or past the east limb that has not yet been assimilated into the surface-flux model that comprises the lower-boundary condition of the PFSS extrapolation.…”
Section: Comparisons With Coronal Holesmentioning
confidence: 99%